DEVELOPING CRITICAL THINKING THROUGH DEBATES IN ENGLISH CLASSES (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2025)
This study examines how debates in English classes develop students’ critical thinking and communication skills. It is relevant for promoting active learning and problem-solving. The research explores debate strategies, formats, and assessments to enhance reasoning. Its novelty lies in combining language learning with higher-order thinking, showing that structured debates effectively foster analytical and reflective skills.